Sustainable Digital Innovation for the Empowerment of Environmentally Friendly Batik MSMS'e - Praswati, Aflit Nuryulia; Anisa Ur Rahmah; Hardika Dwi Hermawan; Aysa Nur Cahyani; Syakila Eka Putrisari Sabarwo (Abdi Psikonomi, 2025)
This Community Service Program aims to improve the competitiveness of batik SMEs in Desa Jarum, Klaten, by adopting environmentally friendly digital technology and supporting the regeneration of young batik artisans. The implementation method includes digital marketing training, financial management, batik training, and batik waste management. The partners involved are Paguyuban ARUMCAWERASA, the Government of Desa Jarum, and BUMDes Jarum, with participants predominantly female (80%) and aged between 25-50 years. Evaluation and monitoring were carried out through pre- and post-training surveys, observations, and interviews. The results showed an 85% increase in participants' knowledge and skills, as well as a 15-20% increase in batik product sales within one month. This program successfully introduced digital technology for marketing and business management while supporting the regeneration of young batik artisans. In conclusion, this program has provided a positive impact on the Batik SMEs of Desa Jarum and can serve as a model for SME development based on technology in the digital era.